Effects of exercise on HDL functionality. Issue 1 (February 2019) - Ruiz-Ramie, Jonathan J.; Barber, Jacob L.; Sarzynski, Mark A.
Abstract : Purpose of review: Low HDL-cholesterol (HDL-C) levels are a strong predictor of cardiovascular disease risk and can be improved with regular exercise. However, raising HDL-C levels pharmacologically has not shown convincing clinical benefits. Thus, research has recently focused on identifying therapies that improve HDL function, with exercise representing such a potential therapy. The purpose of this review is to summarize the effects of exercise interventions on HDL function. Recent findings: The effects of exercise and lifestyle interventions on the primary atheroprotective functions of HDL are reviewed, namely, cholesterol efflux, antioxidative, and anti-inflammatory properties. Differences in study design, study population, and assays are discussed to aid in the interpretation of the reviewed studies. Summary: There is mixed evidence that regular aerobic exercise improves cholesterol efflux capacity, with recent research suggesting an exercise dose threshold needs to be exceeded to produce beneficial effects. There is preliminary evidence that exercise improves the antioxidative and anti-inflammatory properties of HDL. Although exercise represents a potential therapeutic approach to improve HDL function, the heterogeneity and/or lack of findings warrants more and larger studies to determine what HDL function(s) are most responsive to regular exercise and what dose of exercise elicits the greatest improvements in HDL functionality.